INTERNALISASI EKSEKUSI JAMINAN HAK TANGGUNGAN DALAM PEMBIAYAAN KREDIT PADA BANK SYARIAH INDONESIA (BSI) KOTA MALANG: The Internalization of Guarantee Rights Execution in Credit Financing at Indonesian Sharia Bank (BSI) Malang City - Iva Mala; Arini Putri; Aminah Firdausi; Kadek Renitayani (Qawanin: Jurnal of Economic Syaria Law, 2022)
The Financial Institution under the government and supervised by the OJK regarding credit financing in accordance with sharia provisions is the Indonesian Sharia Bank. This study uses a normative juridical approach with a descriptive approach, primary data sources and secondary data from documentation and legislation. The technique in this study uses observation and interviews. The results of this study used the internalization of the Law of the Republic of Indonesia Number 21 of 2008 concerning Islamic Banking and the Law of the Republic of Indonesia Article 6 concerning Mortgage Rights. The obstacles faced in this study are the delinquency of various characteristics of debtors who ignore their installments. Efforts made to overcome these problems are through mediation, fostering to sell the object of mortgage guarantee together and if this method does not produce results, it will be carried out with a court decision. It is hoped that the increase in the survey of the object of the mortgage guarantee can be evaluated again before approving the loan application from the debtor.